2010
DOI: 10.1111/j.1470-6431.2010.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of farmers' markets visitors' needs and wants: the case of Alabama

Abstract: Many studies refer to the importance of farmers' markets for both food producers and for visitors. For producers, the ability to obtain higher returns and/or market part of their produce as value‐added products can be strong incentives, while for consumers benefits include having access to fresher, often tastier foods or simply visiting as a social activity. Relatively few studies, however, explore visitors' needs and wants with regards to their farmers' market experience, that is, from visitors' perspective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 24 publications
(41 reference statements)
3
50
0
Order By: Relevance
“…Farmers must provide customers benefits in return for loyal support, which is consistent with SET (Cropanzano & Mitchell, ; Emerson, ; Roloff, ). Farmers provide access to a food supply that consumers perceive as high quality (Brown, ; Feagan & Morris, ), environmentally friendly (Alkon, ; Garner, ), and healthy (Alonso & O'Neill, ; Brown, ; Myae & Goddard, ). Farmers also provide customized service to loyal customers.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers must provide customers benefits in return for loyal support, which is consistent with SET (Cropanzano & Mitchell, ; Emerson, ; Roloff, ). Farmers provide access to a food supply that consumers perceive as high quality (Brown, ; Feagan & Morris, ), environmentally friendly (Alkon, ; Garner, ), and healthy (Alonso & O'Neill, ; Brown, ; Myae & Goddard, ). Farmers also provide customized service to loyal customers.…”
Section: Discussionmentioning
confidence: 99%
“…Food prices were identified as both being fair and reasonable 50,64-73 and too expensive. 45,47,50,65,66,69,[74][75][76][77][78] Price was identified as not being a concern related to farmers' market use in six studies, 45,49,50,70,78,79 whereas no low-income studies reported this finding. Acceptance of food assistance benefits at farmers' markets was not identified as a key factor related to market use among any of the studies of middle-to highincome or nonspecified-income populations.…”
Section: Economic Facilitators and Barriersmentioning
confidence: 99%
“…Sustainability is a linchpin of many farmers’ markets, and some argue that sustainability is a reason why direct, alternative markets have grown recently in the United States (US), Canada, New Zealand, and the UK (Betz & Farmer, ; Brown, ; Carey, Bell, Duff, Sheridan, & Shields, ; Guthrie, Guthrie, & Lawson, ; Lawson, Guthrie, Cameron, & Fischer, ; Smithers, Lamarche, & Joseph, ; USDA, , ). Customers attend markets for many reasons: to get fresh food (Alonso & O'Neill, ; Brown, ; McNeill & Hale, ; Trobe, ), to encourage sustainable farming practices (Alkon, ; Garner, ), to support local farms economically (Brown & Miller, ; Lyson, Gillespie, & Hilchey, ), to build community ties (Feagan & Morris, ), have a more personal exchange (Garner, ; Robinson & Hartenfeld, ), and express their morality or ethics (Garner, ; McEachern, Warnaby, Carrigan, & Szmigin, ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, consumers often equate farmers’ market food consumption with sustainability initiatives (Alkon, ; Alonso & O'Neill, ; Garner, ; Hunt, ). However, not all farms are equal in terms of applying environmental friendly practices, and consumers are not necessarily well educated on these issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation